Laparoscopic Management of Strangulated Broad Ligament Hernia - Tanvi Khetan; Abdulzahra Hussain; Ihsan Al-Shoek; Shamsi EL-Hasani (Baqiyatallah University of Medical Sciences, 2018)
Introduction: Broad ligament hernia was first reported post-autopsy by Quain in 1861. In a 1995 review article, only 61 cases had ever been reported. This paper presents a case report of broad ligament hernia and explores the literature surrounding this topic. Case Presentation: The patient presented with no significant past medical history, acute lower abdominal pain (several hours), nausea, and vomiting. Clinical examination showed a heart rate of 85 beats per minute; normal temperature, blood pressure, and respiratory rate; and a mildly distended abdomen with tenderness across the right lower quadrant. A plain abdominal X-ray showed dilated small bowel loops, and a blood test showed leukocytosis. Urgent diagnostic laparoscopy showed a broad ligament strangulated hernia with small bowel infarction. Reduction of the small bowel, resection, and side-side anastomosis were performed. The patient had an uneventful recovery, and follow up reported no postoperative complications. Conclusion: Laparoscopic management of small bowel obstruction due to broad ligament internal hernia is a safe and effective option.